(untitled) (Bioagro, 2020)
Cassava has gained importance in the starch industry, concentrated for animal feeding, and in different culinary uses, with increasingly quality requirements. However, many cassava producing areas in Latin America are located in low or sporadic rainfall zones, thus affecting the quality of the root. The objective of this study aimed the evaluation of the culinary quality of this crop (percentages of dry matter, total carbohydrates, starch, ash, and crude fiber) under different irrigation regimes. Thus, an experiment was carried out under split plot design with three replications to evaluate four clones and four irrigation treatments (25, 50, 75, and 100 % of the crop evapotranspiration, Etc). The roots of all the clones showed an adequate content of dry matter. Concha Rosada and Mven 77-3 presented the highest percentages of total carbohydrates and starch, and Bolívar 32 the lowest values. The percentages of both variables increased when the irrigation volumes decreased. The percentages of ash were adequate but the fiber percentages were high. Higher ash contents implied lower fiber content, and viceversa, and irrigation treatments did not show a definite trend for these variables.